How To Increase Income Through Cross Training System Skill On MSME Depok - Sarah Amalia; Agus Sutisna; Deni Deni (Perhimpunan Sarjana Ekonomi dan Bisnis, 2022)
Human resource management that is not carried out in an organized manner will certainly be a problem in businesses run by MSMEs. Human resource development needs to be carried out to increase effectiveness in MSME activities, one of the alternative HR management during the pandemic that can provide added value so that it is beneficial for MSME activities themselves. One of the developments that can be done is to add competence between one part and another or cross training. Seeing the problems faced, the steps taken to achieve the goals and objectives of this activity, an approach was held to related institutions, namely the community of MSME actors through workshops and socialization and training in the form of explanations on the application of management knowledge in financial technology-based financial management in efforts and strategies to realize MSMEs are prosperous and independent. After the cross training, the percentage of participants with more than one skill increased to 70%. Through the addition of the skills of MSME participants, it was found that the daily output increased by 70 to 80 packs per day. However, based on the questionnaire, it can be seen that there are skills that cannot be developed only through the cross training method. The general purpose of this community service activity is to provide practical training and knowledge of human resource management in improving skills among employees which has an impact on increasing the profits of MSMEs who are members of the West Java Champion MSMEs. The method used is a survey method and delivery of materials online and offline as well as simulations and discussions on human resource management. The conclusion of this community service is that there will be assistance in human resource management in the development of Micro, Small and Medium Enterprises in an effort to realize the welfare of the people of Depok City, especially the MSME activist community.